El incipiente crimen organizado nacional y sus verdugos, los improvisados sicarios - Rodríguez Hurtado, Mario Pablo (Pontificia Universidad Católica del Perú, 2015)
A criminal modality that is becoming increasingly important nowadays and has many victims is the contract killing or the use of hitmen. The situation is aggravated by the presence of a process of crime institutionalization. The Peruvian government has responded to this problem typifying the aforementioned crime in the Criminal Code under condemns with are becoming longer. Was this the best solution?In the present article, the author answers this question by analyzing the penal types of contract killing while making a critic of the national criminal policy, taking into account the existence of other criminal types and other possible solutions, to finally prove its futility.

Una modalidad criminal que en el presente está cobrando importancia y muchas víctimas es el asesinato a sueldo o sicariato; situación que se agrava por la presencia de un proceso de institucionalización del crimen. El gobierno peruano ha respondido a este hecho tipificando dicho delito en el Código Penal bajo penas cada vez mayores. ¿Ha sido esta la mejor solución?En el presente artículo, el autor responde a dicha cuestión analizando los tipos penales del sicariato mientras realiza una crítica a la política criminal nacional, teniendo en cuenta la existencia de otras figuras penales y otras posibles soluciones, para finalmente demostrar su inutilidad.
The incipient national organized crime and its executioners, the improvised hitmen
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01